Inka state warehouses in the upper valley of the Chillón river: The case of Pauca Alto (Canta, Lima) - Ricci Jara, Kevin Luis (2021)
Pauca Alto was a collection center that was articulated to other local and state facilities in the upper valley of the Chillón River, for the reception, storage, and transfer of products into the territory of Canta, and subsequently to the central highlands, as part of a strategy of exploitation of the local organization and its resources.